2009
DOI: 10.1519/jsc.0b013e3181876ad0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Anaerobic Water Polo-Specific Tests With the Wingate Test

Abstract: Usage of any items from the University of Cumbria's institutional repository 'Insight' must conform to the following fair usage guidelines.Any item and its associated metadata held in the University of Cumbria's institutional repository Insight (unless stated otherwise on the metadata record) may be copied, displayed or performed, and stored in line with the JISC fair dealing guidelines (available here) for educational and not-for-profit activities provided that• the authors, title and full bibliographic detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…Many studies have used Wingate Test [15,16] and modified Wingate Test [17], to evaluate physiological responses to anaerobic exercise. In our study we evaluate the response to anaerobic exercise before and after hydration with a bicarbonate-calcic mineral water, named Acqua Lete, compared to very low mineral content water (dry residues 14.3 mg/L).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have used Wingate Test [15,16] and modified Wingate Test [17], to evaluate physiological responses to anaerobic exercise. In our study we evaluate the response to anaerobic exercise before and after hydration with a bicarbonate-calcic mineral water, named Acqua Lete, compared to very low mineral content water (dry residues 14.3 mg/L).…”
Section: Discussionmentioning
confidence: 99%
“…While general fitness tests (i.e. general motor and/or endurance capacities) are important indices of overall fitness status and allow a comparison of athletes from different sports (Frenkl et al, 2001), specific fitness tests allow a more precise insight into sport-specific capacities and therefore provide a basis for comparing athletes in the same sport (Bampouras and Marrin, 2009; Holloway et al, 2008; Hughes et al, 2003; Sattler et al, 2011). However, there is a clear lack of studies dealing with specific physical fitness profiles in water polo and, in particular, we found no study which has investigated this problem among high-quality junior water polo players.…”
Section: Introductionmentioning
confidence: 99%
“…Although some validity studies showed a good correlation between mechanical parameters measured during the WAT and strength, speed, power, or agility (13,24,28), other investigations reported an absence of relationship between these variables and/or the incapacity of the WAT to discriminate between elite and nonelite athletes (2,10,17,26,32). Consequently, these authors criticized the ecological validity of the WAT, referring in particular to the discrepancies in the movement patterns and/or muscular mass involved in the test compared with real competition.…”
Section: Introductionmentioning
confidence: 99%